2018
DOI: 10.15576/asp.fc/2018.17.4.109
|View full text |Cite
|
Sign up to set email alerts
|

Wood Pastures in Central Slovakia – Collapse of a Traditional Land Use Form

Abstract: Wood pastures with pollard trees have been a common land-use type across Europe. The trees, besides having positive environmental effects on livestock, served as important source of fodder and wood. Pollarded wood pastures were hence a multifunctional, state of the art, highly productive farming ecosystems. Despite relatively drastic treatment, the trees regenerated quite well, and grew to relatively high-age. When pollarding lapses for longer period the wood pasture may confusingly resemble an ancient forest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Wood-pastures in Europe are models/archetypes of High-Nature Value (HNV) farmland, which hold a unique biodiversity value and are socially and culturally important [1][2][3][4]. In other words, these are complex socio-ecological systems, products of the long-term interaction between society and the surrounding landscape [5].…”
Section: Introduction 1wood-pasture Coverage In Europementioning
confidence: 99%
“…Wood-pastures in Europe are models/archetypes of High-Nature Value (HNV) farmland, which hold a unique biodiversity value and are socially and culturally important [1][2][3][4]. In other words, these are complex socio-ecological systems, products of the long-term interaction between society and the surrounding landscape [5].…”
Section: Introduction 1wood-pasture Coverage In Europementioning
confidence: 99%
“…The Swiss Alps have a long history of forest grazing [22]. Wood pastures are a distinguishing feature of the traditional European rural landscape [23]. Other significant factors of forest loss and degradation in the Siwaliks and midhills include overgrazing, which is a major driver in Nepal's Siwaliks and high highlands [24].…”
Section: Introductionmentioning
confidence: 99%
“…Wood-pastures represent a distinctive element of the traditional European rural landscape (Wiezik et al, 2018). They have had an essential role in supporting raising extensive livestock Hartel, Plieninger, & Varga, 2015;Roellig et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, rapid land cover changes occur in wood-pastures all over Europe under pressure from various drivers. The persistence of wood-pastures is challenged by abandonment and management changes (Hartel et al, 2013;Hartel & Plieninger, 2014;Hartel et al, 2015Hartel et al, , 2017Pereponova & Skaloš, 2019;Plieninger et al, 2015;Wiezik et al, 2018). Studies on long-term land cover change showed that the woody vegetation cover in the Carpathian Mountains increased because of the abandonment of farming (Griffiths, Müller, Kuemmerle, & Hostert, 2013;Kuemmerle, Müller, Griffiths, & Rusu, 2009;Munteanu et al, 2014;Vanonckelen & Van Rompaey, 2015).…”
Section: Introductionmentioning
confidence: 99%